2016
DOI: 10.1126/science.aad0591
|View full text |Cite
|
Sign up to set email alerts
|

An aromatic ion platform for enantioselective Brønsted acid catalysis

Abstract: Chiral acid catalysts are useful for the synthesis of enantioenriched small molecules, but the standard catalysts require laborious and expensive preparations. Here, we describe a chiral Brønsted acid prepared in one step from naturally occurring (-)-menthol and readily available 1,2,3,4,5-pentacarbomethoxycyclopentadiene. Aromatic stabilization serves as a key contributing factor to the potent acidity of the resulting compound, which is shown to catalyze both Mukaiyama-Mannich and oxocarbenium aldol reactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
85
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(88 citation statements)
references
References 54 publications
1
85
0
2
Order By: Relevance
“…Another prominent class of anionic Cps are the pentacarboxycyclopentadienes (PCCPs). These were recently found to be very efficient Bronsted acid catalysts when derivatized with chiral substituents . In a subsequent report, Lambert and co‐workers described the preparation of a series of differently substituted PCCPs (Scheme B), expanding the scope of their original work significantly …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another prominent class of anionic Cps are the pentacarboxycyclopentadienes (PCCPs). These were recently found to be very efficient Bronsted acid catalysts when derivatized with chiral substituents . In a subsequent report, Lambert and co‐workers described the preparation of a series of differently substituted PCCPs (Scheme B), expanding the scope of their original work significantly …”
Section: Discussionmentioning
confidence: 99%
“…These were recently found to be very efficient Bronsted acid catalysts when derivatized with chiral substituents. [42] In as ubsequentr eport, Lambert andc o-workersd escribed the preparation of as eries of differently substituted PCCPs (Scheme 11 B), expanding the scope of their originalwork significantly. [43] An interestingp rospectt hat the anionic Cps open up is their potentials olubility in water.B eing able to preparep olysubstituted and water-soluble Cps and metal complexes would be desirable from agreen-chemistry point of view.Additionally, for some groups it is also favorable for the preparation of 99m Tc complexes,w hichf requently feature Cp-ligands and all reactions need to be conducted in water because the product is directly used for radioimaging in patients.…”
Section: Chiralc Psmentioning
confidence: 99%
“…[33] It was estimated that compounds similar to 70 possess strong acidity (pK a % 8. [33] It was estimated that compounds similar to 70 possess strong acidity (pK a % 8.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…10 The motivation for this work was a desire to identify a catalytic platform that would be trivial to synthesize and simple to diversify, and that might offer unique opportunities for transition state stabilization. In the course of this work, we found that while 1,2,3,4,5-pentacarbomethoxycyclopentadiene ( 2 ) was readily available on a preparative scale (Figure 1b), there was a dearth of synthetic procedures to access derivatives of this core material.…”
mentioning
confidence: 99%